2013
DOI: 10.1016/j.geoderma.2013.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tillage effects on the spatial variation of soil properties using ground-penetrating radar and electromagnetic induction

Abstract: Tillage practices influence physical, chemical, and biological soil properties, which also affect soil quality and consequently plant growth. In this study, the main objective was to evaluate the effects of different tillage practices on soil physical properties such as soil water content (SWC) by using geophysical methods, namely, ground-penetrating radar (GPR) and electromagnetic induction (EMI). Additional measurements such as soil sampling, capacitance probe, and soil penetrometer data were acquired as gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…reported that the average corn yield (7.26 ton/ha) from 1993 to 1999 in non-tillage is higher than in spring plow tillage (6.42 ton/ha)40. The major reason could be that the CT treatment decreased soil bulk density and soil moisture content, and as a result, decreased corn root growth and yield4142. There are also a few studies reporting that no-tillage does not change or even decreases crop yield4043.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the average corn yield (7.26 ton/ha) from 1993 to 1999 in non-tillage is higher than in spring plow tillage (6.42 ton/ha)40. The major reason could be that the CT treatment decreased soil bulk density and soil moisture content, and as a result, decreased corn root growth and yield4142. There are also a few studies reporting that no-tillage does not change or even decreases crop yield4043.…”
Section: Discussionmentioning
confidence: 99%
“…Terms & Conditions of access and use can be found at http:// www.tandfonline.com/page/terms-and-conditions Introduction Scientific information on the spatial variability of soil properties is critical for understanding ecosystem processes, designing sustainable soil-crop systems, and making environmental management decisions (Tesfahunegn et al 2011). Soil penetration resistance (SPR), soil water content (SWC), and other soil properties are affected by the spatial variability of the soil (Jonard et al 2013). SPR can be helpful for choosing an appropriate depth of tillage and intensity of soil crushing, estimating the tillage quality, and developing management options that minimize crop production (Usowicz & Lipiec 2009).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Better description of spatial changes in SPR and SWC due to machinery traffic will allow us to determine the permissible size of agricultural machinery and number of passes to avoid soil degradation and preserve favorable conditions for plant growth (Botta et al 2012). Many previous studies have focused on the spatial variability of SPR and SWC, which largely relies on the use of geostatistics (Özgöz 2009;Aksakal et al 2011;Jonard et al 2013); however, the profile, particularly the horizontal and vertical, distributions of SPR and SWC have not received much attention up to now. The effect of tillage on the spatial variability of SPR and SWC has been evaluated by many researchers, whereas most of these studies are restricted to the variability in the crop row position (Usowicz & Lipiec 2009;Aksakal et al 2011;Millán et al 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Generally, GPR can be used to monitor subsurface features that have contrasting dielectric constants (Truman et al, 1988). In particular, GPR has been used for soil water content estimation including measuring soil water content profile (Lambot et al, 2004), estimating soil water variation under irrigation conditions (Galagedara et al, 2005), identifying specific soil water depth and monitoring spatial and temporal variation of soil water content (Pan et al, 2012), mapping the spatial variation of soil water content at the field scale (Weihermüller et al., 2007), and comparing the tillage effects on soil water content (Jonard et al, 2013). Compared to time domain reflectometry, GPR is better suited for mapping large-scale features (>5 m) in soil water content (Huisman et al, 2002).…”
Section: Sensing Soils and Rootsmentioning
confidence: 99%